Employees' risk taking capabilities and learning organisation: moderating role of organisational size. (23rd April 2019) - Budhiraja, Sunil; Malhotra, Meenakshi; Kaushik, Neeraj
The study aims to assess the moderating role of organisational size in the relationship between employees' risk taking capabilities and learning inside an organisation. A conceptual model has been framed based upon the 'grounded theory' methodology (Strauss and Corbin, 1990). Structural equation modelling (SEM) has been used to assess the model using AMOS (version 20) on 444 valid responses from entry and middle level IT employees. The findings of the study indicate that size of the organisation plays a significant role in leveraging the risk taking capabilities of employees and fostering continuous learning. Further, medium size organisations are doing better in leveraging risk taking capabilities of employees as compared to small and large organisations. The findings of the study shall help IT companies to develop some interventions in order to strengthen the risk taking capabilities of employees and strengthen overall organisational learning. No such effort has been made to assess the role organisational size in the relationship between employee's risk taking capabilities and learning organisation in Indian context. The study shall contribute in the existing literature and help HR practitioners in building successful learning organisation.